An omnidirectional thermal harvester through guiding heat flux based on thermal cloak. (1st March 2023) - Sun, Tao; Zhang, Kai; Sun, Jingyong; Shao, Li-Hua
Highlights: Harvesting thermal energy from omnidirectional directions. The feasibility is demonstrated both theoretically and experimentally. Analytical expressions for temperature distributions are derived. Multilayer structure approximation exhibits excellent harvesting function. The thermal harvesting efficiency is as high as 95%. Abstract: The use of thermal harvesters, including fan-shaped structures and polygonal concentrators, is becoming increasingly prevalent for thermal energy utilization. However, such thermal harvesters either harvest thermal energy in a specific direction leading to inefficient harvesting; or require multiple harvesters arrangement around the heat source leading to the complicated manufacture problems. In this work, we propose an omnidirectional thermal harvester (OTH) through guiding heat flux that can harvest thermal energy from omnidirectional directions. The feasibility of OTH is demonstrated both theoretically and experimentally, by employing a regulation layer with anisotropic thermal conductivity. An alternative design scheme with multilayer structure approximation to construct the OTH has also been presented. The results show that the proposed OTH facilitates efficient thermal energy harvesting with the thermal harvesting efficiency as high as 95%, which is nearly-three times that of the baseline thermal harvester. The OTH has extra advantages with simple structure and naturally accessible materials, which benefit its potential applications in thermal-electric utilization and heat storage.